"Pernicious Publicity": The East India Company, the Military, and the Freedom of the Press, 1818–1823. (October 2022) - Wilkinson, Callie
Abstract: Early nineteenth-century Bengal is frequently used as a case study to demonstrate how debates over press liberties acquired additional stakes in colonial settings. Yet existing scholarship overlooks how the expansion of Britain's military presence overseas during and after the Napoleonic Wars complicated reformist ambitions for a free press. In India, army officers formed a significant proportion of the European population and were both enthusiastic readers of and contributors to the fledgling colonial press. Using the example of the Calcutta Journal, one of India's first daily newspapers, the author shows how the boundaries of what officers could and could not publicize in the press were negotiated through legal proceedings and disciplinary action and through debate within the newspaper itself. The preservation of military discipline was the primary motivation for press regulation during this period, and the military continued to be viewed as an exception to the rule even as commitment to government intervention began to wane. Yet within the military itself, officers strenuously debated their right to speak out and claim their place within the public sphere. These disputes reflect wider divisions within the army and reveal the ambiguous position of Britain's military at a time when the relationship between state and civil society was being reconfigured.